Two-Dimensional Transition Metal Oxide and Chalcogenide-Based Photocatalysts - Haque, Farjana; Daeneke, Torben; Kalantar-zadeh, Kourosh; Ou, Jian Zhen (Nano-Micro Letters, 2017)
Two-dimensional (2D) transition metal oxide and chalcogenide (TMO&C)-based photocatalysts have recently attracted significant attention for addressing the current worldwide challenges of energy shortage and environmental pollution. The ultrahigh surface area and unconventional physiochemical, electronic and optical properties of 2D TMO&Cs have been demonstrated to facilitate photocatalytic applications. This review provides a concise overview of properties, synthesis methods and applications of 2D TMO&C-based photocatalysts. Particular attention is paid on the emerging strategies to improve the abilities of light harvesting and photoinduced charge separation for enhancing photocatalytic performances, which include elemental doping, surface functionalization as well as heterojunctions with semiconducting and conductive materials. The future opportunities regarding the research pathways of 2D TMO&C-based photocatalysts are also presented. Highlights: 1 This review summarizes current two-dimensional (2D) transition metal oxide and chalcogenide (TMO&C)-based photocatalytic systems for hydrogen evolution reactions, organic pollutant degradation, carbon reduction and microbial disinfectants. 2 The influences of unique features of 2D TMO&C in terms of crystal and electronic band structures are reviewed regarding their photocatalytic performances. 3 The improvement strategies of 2D TMO&C photocatalysts including elemental doping, surface functionalization and heterojunction formation are critically discussed.